When Goal-Setting Forges Ahead but Stops Short - Islam, Asad; Kwon, Sungoh; Masood, Eema; Prakash, Nishith; Sabarwal, Shwetlena; Saraswat, Deepak (World Bank, Washington, DC, 2020)
This paper reports the results of an at-scale randomized controlled trial among 18,000 secondary students in Zanzibar (Tanzania) to examine the effects of personal best goal-setting on student outcomes. The paper also tests the impact of combining goal setting with non-financial rewards conditional on students meeting the goals they set. The results suggest that goal-setting has a significant, positive impact on students' time use, study effort, and self-discipline. However, there are no significant impacts on test scores. This is partially because nearly two-thirds of the students do not set realistic goals. The paper finds that the effects on time use, study effort, and discipline are weaker when goal setting is combined with nonfinancial rewards. This suggests that tying goal setting to extrinsic incentives could weaken its impact. The results show stronger impacts for female students and from students from weaker socioeconomic backgrounds. These results demonstrate that goal setting can have positive impacts on student outcomes, especially for the relatively disadvantaged. However, for maximizing the impacts, goal setting may need to be combined with guidance on setting realistic goals, and extrinsic rewards tied to goals may need to be avoided.